Management Of Human Talent And Job Performance Of Administrative Staff In Educational Institutions - Berrocal-Soto, Juan Carlos (2022)
The research sought to know the relationship between the variables human talent management and job performance of administrative staff in educational institutions, for which the type of descriptive research was established in which questionnaires were applied as an instrument that measure the variables investigated and collected information from a sample consisting of 30 workers, likewise, the investigation was carried out from the correlational design. For the processing of the data, the use of the Kendall Tau b statistician was used, in which it is concluded that the management of human talent is directly and significantly related to the work performance of the administrative staff in the educational institutions of the UGEL Huamanga. (Tb=0.763; p= 0.00<0.05).